(untitled) (Bangladesh Journal of Agricultural Research, 2023)
The field evaluation of betel nut germplasm was conducted at Regional Agricultural Research Station, Bangladesh Agricultural Research Institute (BARI), Rahmatpur, Barishal all the year round during three consecutive years of 2019-22 to select suitable entry (ies) for releasing as new variety (ies) for Barishal region. Seven entries of betel nut viz., E1 (AC Rah-01), E2 (AC Rah-02), E3 (AC Rah-03), E4 (AC Rah-04), E5 (AC Rah-05), E6 (AC Rah-06) and E7 (AC Rah-07) were used as testing materials. The germplasm had been collected from different regions of Bangladesh since 1973. Three years average results showed that significant variations were observed among the evaluated betel nut germplasm. The maximum fresh and dry nut yield with husk (34.48 and 12.07 t/ha, respectively) was obtained from AC Rah-02 that was identical to AC Rah-01 (28.24 and 10.57 t/ha, respectively). Results revealed that the three years average yield performances of AC Rah-02 and AC Rah-01 were higher compared to that of other tested entries. Maturing condition of AC Rah-01 was late but early maturity was observed in AC Rah-02 and other tested entries. Nut shapes of AC Rah-01 and AC Rah-02 were oblong and oval, respectively. The laboratory analyses results revealed that alkaloids that caused oral cancer was less (3.95 mg/g) and the Ferric Reducing Antioxidant Power that cures the disease was higher (10.20 mgAAE/g) in AC Rah-01. The amount of total alkaloids (1.35%) and Arecoline content (4.69 mg/g) that cause cancer in the mouth were lower in AC Rah-02. Considering yield potentiality, maturity condition (late and early), lower incidences of insect-pest and diseases, and biochemical properties (higher Antioxidant power and lower contents of Alkaloids or Arecoline), AC Rah-01 and AC Rah-02 have been selected as promising entries of betel nut towards releasing new varieties for Barishal region of Bangladesh. Bangladesh J. Agril. Res. 47(3): 291-302, September 2022